The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1371/journal.pone.0103840
|View full text |Cite
|
Sign up to set email alerts
|

Human CD56+ Cytotoxic Lung Lymphocytes Kill Autologous Lung Cells in Chronic Obstructive Pulmonary Disease

Abstract: CD56+ natural killer (NK) and CD56+ T cells, from sputum or bronchoalveolar lavage of subjects with chronic obstructive pulmonary disease (COPD) are more cytotoxic to highly susceptible NK targets than those from control subjects. Whether the same is true in lung parenchyma, and if NK activity actually contributes to emphysema progression are unknown. To address these questions, we performed two types of experiments on lung tissue from clinically-indicated resections (n = 60). First, we used flow cytometry on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 56 publications
1
60
1
1
Order By: Relevance
“…Our findings contrast with several reports using domestic animal models wherein large increases in CD4 + and CD8 + T-lymphocytes occurred in CL at the onset of regression [5,50]. CD3ε antibody was chosen as a marker of T-lymphocytes in the current study because the CD3ε receptor is expressed selectively by all T-lymphocytes, unlike CD8 which is typically co-expressed with CD16 in primate NK cells [51]. Studies in bovine CL focused on a particular subtype of T-cell, CD8 + γδ T-cells.…”
Section: Discussioncontrasting
confidence: 88%
“…Our findings contrast with several reports using domestic animal models wherein large increases in CD4 + and CD8 + T-lymphocytes occurred in CL at the onset of regression [5,50]. CD3ε antibody was chosen as a marker of T-lymphocytes in the current study because the CD3ε receptor is expressed selectively by all T-lymphocytes, unlike CD8 which is typically co-expressed with CD16 in primate NK cells [51]. Studies in bovine CL focused on a particular subtype of T-cell, CD8 + γδ T-cells.…”
Section: Discussioncontrasting
confidence: 88%
“…104 In humans, lung-associated NK cells respond to influenza A infection by up-regulating degranulation/cytotoxic activation marker CD107a and produce granzyme B and IFN-c, which mediates killing of infected macrophages. 105 Recently, Finch et al 106 showed increased killing of lung epithelial cells by lung NK cells, but not blood NK cells, from patients with COPD was due to DC-NK cell interactions and IL-15a transpriming. CD56 + CD16 + NK cells isolated from the airways of COPD patients have increased natural cytotoxicity in comparison to those from controls, 93 and demonstrate increased killing of autologous lung cells in co-culture experiments.…”
Section: Ilc3smentioning
confidence: 99%
“…CD56 + CD16 + NK cells isolated from the airways of COPD patients have increased natural cytotoxicity in comparison to those from controls, 93 and demonstrate increased killing of autologous lung cells in co-culture experiments. 105 Recently, Finch et al 106 showed increased killing of lung epithelial cells by lung NK cells, but not blood NK cells, from patients with COPD was due to DC-NK cell interactions and IL-15a transpriming. In individuals with asthma, NKs cells in bronchoalveolar lavage fluid are skewed to a cytolytic phenotype and express higher levels of granzyme A.…”
Section: Nk Cellsmentioning
confidence: 99%
“…However, further characterization into CD4 + or CD8 + NKT-like cells was not performed in any of these reports. NKT-like cells have also been reported to be increased in induced sputum and bronchoalveolar lavage (BAL) of COPD patients and, importantly, have been shown to be cytotoxic to autologous lung cells (3, 4, 6). …”
Section: Cd8+ Natural Killer T-like (Nkt-like) Cells In Chronic Obstrmentioning
confidence: 99%